The Implementation of Self-Improvement Strategies in Strengthening School Culture at Muhammadiyah Vocational School 02 Tangerang in the Era of Society 5.0 - Astini, Julia; Makiyah, Ulfah; Asmaenah, Aas; Gibthy, Rizka Maria Al; Triyana, Aditiya; Utaminingsih, Sri; R, Ruknan; Djihadah, Nuryati (Yayasan Daarul Huda Kruengmane, 2025)
This community service initiative was carried out to implement a self-improvement strategy as an effort to strengthen the school culture at SMK Muhammadiyah 02 Tangerang in the era of Society 5.0. In this period of rapid technological advancement, schools are required not only to adapt to digital transformation but also to consistently cultivate character and humanistic values that form the foundation of education. Across many vocational schools, similar challenges tend to emerge, including low levels of student self-awareness, inconsistent discipline, unstable learning motivation, and the inadequate internalization of school values in daily learning activities and interpersonal interactions. These conditions influence students’ readiness to meet the demands of the workforce and navigate the social dynamics of the digital age.To address these issues, the program was designed through a series of activities, including training sessions, workshops, counseling, group discussions, education games, and direct mentoring. All components of the program aimed to foster students’ critical-thinking skills, effective communication, time and emotional management, as well as to enhance their motivation and commitment to continuous self-development. The outcomes indicate that students began to grasp the concept of self-improvement more deeply, demonstrated the ability to engage in self-reflection, identified their personal strengths and weaknesses, and formulated practical steps for more structured personal development. Furthermore, positive changes were observed in several aspects, including discipline, collaboration, participation in school activities, and students’ decision-making abilities.